2018
DOI: 10.3892/ijo.2018.4370
|View full text |Cite
|
Sign up to set email alerts
|

HepaCAM inhibits the malignant behavior of castration-resistant prostate cancer cells by downregulating Notch signaling and PF-3084014 (a γ-secretase inhibitor) partly reverses the resistance of refractory prostate cancer to docetaxel and enzalutamide in vitro

Abstract: Castration-resistant prostate cancer (CRPC) continues to be a major challenge in the treatment of prostate cancer (PCa). The expression of hepatocyte cell adhesion molecule (HepaCAM), a novel tumor suppressor, is frequently downregulated or lost in PCa. Overactivated Notch signaling is involved in the development and progression of PCa, including CRPC. In this study, we found that the activities of Notch signaling were elevated, while HepaCAM expression was decreased in CRPC tissues compared with matched prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…The LNCaP cell line was obtained from American type culture specimens. To induce resistance, LNCaP cells were cultured in drug resistance media (39)(40)(41). Cells exhibiting bicalutamide resistance were named R-Bica cells and LNCaP cells resistant to bicalutamide and docetaxel were named R-B+D cells as previously described (41).…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The LNCaP cell line was obtained from American type culture specimens. To induce resistance, LNCaP cells were cultured in drug resistance media (39)(40)(41). Cells exhibiting bicalutamide resistance were named R-Bica cells and LNCaP cells resistant to bicalutamide and docetaxel were named R-B+D cells as previously described (41).…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…The membrane was incubated overnight with the following primary antibodies: K-Ras, PLCε, and PKCε (Santa Cruz); and VEGF, MMP2, MMP9, and β-actin (Cell Signaling Technology). Next, the membrane was incubated with secondary antibody for 2 h, and finally visualized by Enhanced Chemiluminescence (41,44). Image-Pro Plus 6.0 software was used for detecting protein band intensity.…”
Section: Western Blot Assaymentioning
confidence: 99%
“…PF-03084014 is a small molecule reversible, non-competitive and selective GSI, which has been shown to inhibit Notch pathway through blocking cleaved-notch receptor formation in various types of cancer [14,[22][23][24]. Recently, a few studies have found that inhibition of Notch signaling using PF-03084014 sensitized DOX-resistant prostate cancer cells to DOX [12,25]. However, it is not completely clear that pharmacological targeting of the Notch pathway by PF-03084014 could impact DOX chemoresistance in prostate CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…GlialCAM (also called HepaCAM) was identified as a putative tumour suppressor gene that is silenced in hepatocellular carcinoma [ 278 ]. GlialCAM downregulation is observed in liver, bladder, prostate, kidney, breast, uterus, colon, stomach, and rectal cancer biopsies [ 269 , [278] , [279] , [280] , [281] , [282] ]. Functionally, when GlialCAM is expressed in the liver carcinoma cell line HepG2, cell motility and adhesion are increased, colony formation is reduced, and proliferation is reduced [ 278 ].…”
Section: − Channelsmentioning
confidence: 99%